Gandaki Sampada: a new litchi variety - Nath, Vishal; Gupta, A K; Pandey, S D; Srivastava, Kuldeep; Singh, Awatar; Mishra, D S (Indian Horticulture, 2019)
A high-yielding and high pulp containing variety, Gandaki Sampda, of litchi has been developed by ICAR-NRC for Litchi. It is a late-maturing clone that ripen during mid-June. Fruits are large in size (35-42g), conical in shape, vermilion to carmine colour at maturity with dark blackish brown tubercle. Pulp is creamy-white, soft, juicy with pleasant aroma. The variety is resistant to fruit cracking and has good yield potential (120-140 kg/tree). It has very high percentage of shrivelled and small seeded fruits which result in 80-85% pulp recovery. This clone is highly adaptive to Indo-Gangetic plain.